Towards Multi-Stakeholder Clouds - Borysei, Bohdan; Saroiu, Stefan; Lara, Eyal de (HotMobile, 2024)
Cloud providers are embracing edge computing by developing multi-stakeholder clouds (MClouds), in which the infrastructure is shared among cloud providers, hosting site operators, and, sometimes, system integrators. This form of sharing creates a new set of challenges around infrastructure management. Unfortunately, traditional resource management methods based on partitioning and virtualization do not fit well the needs of infrastructure management in a multi-stakeholder scenario. Our paper describes these new set of challenges, and puts forward a new authorization framework based on two-person control (P2C).